Pengukuran Nilai Keseimbangan Gerakan Manusia terhadap Dataset Tari Remo dengan High-level Matrix/Array Language - Shierly Kartika Salim; Lukman Zaman; Endang Setyati (J-INTECH ( Journal of Information and Technology), 2023)
Remo Dance is one of Indonesia’s traditional dance that originated from East Java and need to be preserved. The preservation act from collaboration of the Goventment and the Society started with a mass Remo Dance at Surabaya city on the year of 2022 that successfully granted a MURI record. This research is meant to support all the effort by calculating balance of the movements as one of the aspect of biomechanics. Biomechanics it self is a branch of study that learns about movement mechanism of living organism. The calculation of balance as an ability to keep a posistion on the change of movements is aim to analyze which movements has the most difficulty in balance and which one is the most stable from the chunk of motion capture data. Computation is done with high-level matrix/array language and the data form is a biovision hierarchy file (BVH). The Visualization of data shows that ‘ucek-ucek’ motion is the most stable movements, while 360 degree spin motion is a difficult movements and require great balance.